Analysis of Regulation of Residential Suburbanisation in Hinterland of Post-socialist ‘One Hundred Thousands’ City of České Budějovice - Kubeš Jan (Bulletin of Geography. Socio-Economic Series, 2015)
Residential suburbanisation is currently the most important urbanisation process transforming metropolitan areas in European post-socialist countries, especially in Central Europe and at Baltic states. The paper compares the statements of the mayors of the suburban municipalities situated in the hinterland of the city of České Budějovice (a one-hundred-thousand city in the South-West of the Czech Republic) and also the local building officials, spatial planning ofcials and experts regarding the recent, currently on-going and upcoming construction of houses in the suburbs and the regulation of these constructions. Further, it discusses the possibilities of influencing the construction of the houses through the spatial plans of municipalities, settlement zones, and metropolitan areas. The interviewed mayors consider, rather uncritically, the recent large construction of houses in their suburbs in general as appropriate. One third of the mayors, however, do not want any further suburban development of this kind. Spatial planning officials and building officials do not have sufficiently powerful tools to influence the extent of the construction and the designs of houses in the individual suburban municipalities and their suburbs. Some of them, together with the experts, support the reintroduction of the metropolitan area spatial plan.